DISTANCE ESTIMATION TO THE INTERPHASE-FAULT LOCATION IN THE DISTRIBUTIVE AIR-LINE GRIDS BASED ON ANALYSIS OF THE HARMONIC COMPONENT PARAMETERS OF THE OPERATING EMERGENCY CONDITIONS - E. V. Kalentionok; Ye. O. Yakovchits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Most techniques of the fault location based on the one-side measurement of the emergency mode characteristics use the short-circuit steady-regime parameters in the fundamental mode frequency. This approach compels to seek additional devices for tuning out the loadings of transformer-substations. Besides, it is susceptible to the nonlinearity effect of closed-circuit arc in the fault location which significantly reduces the accuracy of the remote location of the failure.For estimating the distance to the location of interphase failure on the aerial distributive transmission lines the article proposes a new technique employing the harmonic components of the operating emergency parameters. The algorithm of the present method realization includes: taking down oscillograms of the emergency-mode parameter values (e. g. in doublephase failure – the short-circuit current, the linear voltage between the faulty phases) with necessary discretization interval; expansion of the operating emergency parameters in a Fourier series (realized with a quick Fourier expansion algorithm); estimating the distance to the fault location by the analytical expression; performing the statistical analysis of a row of distance values and finding the most probable distance to the fault location.For effectiveness investigation of the proposed method of trapping harmonic components the paper considers a 10 kV distributive electrical grid feeding nine transformer substations. The authors performed calculation of normal and emergency modes utilizing computer program MatLab in dynamic simulating environment Simulink. The arc is represented by a block describing the linearized dynamic volt-ampere characteristic of the arc. The built characteristic curves demonstrate dependence of the fault-location distance value from the frequency at which this value is obtained and the number if its reiterations. Based on the calculations, the authors establish that the accuracy of the distance determination to the interphase fault location depends on the oscillograph-discretization interval, the duration and the record-start delay of the operating emergency parameters.